SALES MANAGEMENT ANALYSIS AND DECISION MAKING - S. Sangadji, Suwandi (PT. Sangadji Media Publishing, 2023)
This comprehensive book aims to provide readers with an in-depth understanding of sales management, covering analysis and decision-making for developing effective sales strategies and tactics. It also delves into various concepts, techniques, and tools used in sales management and how to apply them in practice. The book covers topics such as personal selling, organizational strategies, sales organization structure, salesforce deployment, recruitment and selection, sales training, sales leadership, motivation and reward systems, evaluating organizational effectiveness, and evaluating salesperson performance. Additionally, it explores the role of personal selling in marketing, highlighting the difference between trust-based selling and transactional selling. The book emphasizes the importance of customer value in sales strategy and adaptive selling. Current trends in sales professionalism, such as complexity, collaboration, and accountability, are also discussed. Organizational strategy's impact on the sales function is examined, along with the allocation of sales efforts and territory design. The importance of recruiting the right sales talent and the significance of sales training for both newly recruited and existing sales force members are emphasized. Sales leadership and management are explored, considering situational factors influencing effective leadership approaches. The book also delves into motivation management and reward systems, detailing various financial and non-financial rewards that motivate salespeople. Evaluating the effectiveness of sales organizations and salesperson performance are also discussed, along with various evaluation methods. Overall, this book provides valuable insights and practical guidance for sales managers, sales management students, and anyone seeking to enhance their sales performance. Ingram et al. have skillfully written this book, offering a comprehensive resource for navigating the complexities of sales management.